1993
DOI: 10.1016/s0248-4900(05)80196-0
|View full text |Cite
|
Sign up to set email alerts
|

Bistramide A‐induced irreversible arrest of cell proliferation in a non‐small‐cell bronchopulmonary carcinoma is similar to induction of terminal maturation

Abstract: Bistramide A, a new toxin isolated from a New Caledonian Urochordata, shows an antiproliferative effect on a non-small-cell lung carcinoma line in vitro and G1-blockade. In this work, the growth arrest induced by bistramide A was shown to be irreversible as assessed by growth kinetics of pretreated cells. Furthermore, the drug caused an underexpression of the nuclear antigen Ki67. These events are similar to a G1-differentiation cell cycle step blockage and a terminal maturation induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In the absence of C(1)-C(4)-enone, analogs 4 and 5 are expected to be much less effective at sequestering monomeric actin due to reversible G-actin binding and competition with a range of other actinbinding proteins in the cell. Although additional studies of antitumor effects of bistramides are required, our results could help explaining the reported differences in the abilities of bistramides A, D, and K to inhibit tumor growth in vivo (20). The high toxicity of bistramide A in vivo could be explained by facile delivery of this compound into vital organs due to the covalent interaction with its protein target, which is abundant in healthy tissues.…”
Section: Mechanism Of Action Of Bistramide Amentioning
confidence: 66%
See 1 more Smart Citation
“…In the absence of C(1)-C(4)-enone, analogs 4 and 5 are expected to be much less effective at sequestering monomeric actin due to reversible G-actin binding and competition with a range of other actinbinding proteins in the cell. Although additional studies of antitumor effects of bistramides are required, our results could help explaining the reported differences in the abilities of bistramides A, D, and K to inhibit tumor growth in vivo (20). The high toxicity of bistramide A in vivo could be explained by facile delivery of this compound into vital organs due to the covalent interaction with its protein target, which is abundant in healthy tissues.…”
Section: Mechanism Of Action Of Bistramide Amentioning
confidence: 66%
“…In addition, we demonstrated that the C(1)-C(4) enone-containing subunit of this natural product plays a pivotal role in covalent modification of cellular actin, which further enhances the cytotoxicity of the corresponding bistramide-based compounds. Our study provides comprehensive characterization of the unique mode of action of bistramide A and identifies structural requirements of bistramides that are responsible for severing actin filaments and inhibiting growth of cancer cells in vitro and in vivo (18)(19)(20).…”
mentioning
confidence: 99%
“…As this metabolic way is very highly regulated, it suggests that drugs could probably act through numerous different mechanisms. Over the last years, we have developed an approach involving the screening and purification of new substances able to block the multiplication of the cells in G0/G1 phases (Deslandes et al, 2000;Carbonelle et al, 1999;Bergé et al, 1997;Riou et al, 1996;Ziddane et al, 1996;Bourgougnon et al, 1994;Riou et al, 1993). The present study investigated the in vitro effects of the extract from the brown seaweed Bifurcaria bifurcata on the NSCLC-N6 line.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule was initially isolated in 1988 from the marine ascidian Lissoclinum bistratum 11 and four other members of the bistramide family (bistramides B, C, D and K) have been identified to date 12. Bistramides exhibit significant biological properties, in particular, antiproliferative,13 neurotoxic14 and cytotoxic12 activities. More specifically, the potent antiproliferative profile of bistramide A was initially attributed to a highly selective activation of protein kinase C‐δ 15.…”
Section: Introductionmentioning
confidence: 99%